One-pot preparation of 4-aryl-3-bromocoumarins from 4-aryl-2-propynoic acids with diaryliodonium salts, TBAB, and Na2S2O8 - Sasaki, Teppei; Moriyama, Katsuhiko; Togo, Hideo (Beilstein Journal of Organic Chemistry, 2018)
Various 4-aryl-3-bromocoumarins were smoothly obtained in moderate yields in one pot by treating 3-aryl-2-propynoic acids with diaryliodonium triflates and K2CO3 in the presence of CuCl, followed by the reaction with tetrabutylammonium bromide (TBAB) and Na2S2O8. The obtained 3-bromo-4-phenylcoumarin was transformed into 4-phenylcoumarin derivatives bearing C–H, C–S, C–N, and C–C bonds at 3-position.
Keywords: 3-aryl-2-propynoic acid; bromo-cyclization; coumarin; diaryliodonium triflate; O-phenylation